Pathology of heart, coronaries and aorta in autopsy cases with history of sudden death: an original article - Sonawane, Sushil Y.; Matkari, Pushkar P.; Pandit, Gopal A. (International Journal of Research in Medical Sciences, 2017)
Background: Natural deaths represent a large proportion of sudden (unexpected and unattended) deaths. The term “sudden cardiac death” (SCD) refers to death from the abrupt cessation of cardiac function due to cardiac arrest. The objective of this study was to identify various causes, risk factors, age and sex distribution associated with sudden cardiac death in an Indian setting. Methods: Detail review of medical records and an autopsy study of all cases of sudden cardiac death that occurred instantaneously or within 24 hours of onset of symptoms in a tertiary care institution, between December 2010 and December 2015 was carried out. Results: In total, 124 cases of sudden death were studied during this period. Out of 124 cases, 109 cases (87.90%) showed pathology in heart and aorta. Atherosclerotic coronary heart disease was the most common cause of death (72.58%) followed by Hypertensive heart disease (4.83%), Hypertrophic cardiomyopathy (3.22%), Myocarditis (3.22%), Infective endocarditis (1.61%), Rheumatic heart disease (0.8%), Aortic dissection (0.8%), and syphilitic aortitis (0.8%). Conclusions: Sudden death is a source of concern and a detailed postmortem examination is mandatory to ascertain its cause. Presence of co-existing conditions like diabetes and hypertension contribute immensely to the risk of sudden death. Occurrence of sudden death at a younger age presents a formidable challenge. Prevention of development of risk factors of atherosclerosis at an early age can be an effective strategy to counter this ailment at all levels.